The Intersection between Linguistic Theories and Computational Linguistics over time - Moreira, Alexandra; Oliveira, Alcione; Possi, Maurílio de Araújo (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
Recent achievements have turned Computational linguistics into a dynamic research area, and an important field of application development that is being explored by leading technology companies. Despite the advances, there is still much room for improvement to allow humans to interact with computational devices, through natural language, in the same way that humans interact with native speakers of the same language. How to make computers understand or create new metaphors, metonymies or other figures of language? Is it possible to develop natural language systems capable of producing lyrics or poetry on the same level as humans? Can we produce systems capable of assigning new meanings to syntactic elements that are immediately perceived as coherent by humans? In this paper, we account for the evolution of computational linguistics, drawing a parallel with the evolution of linguistic theories and speculating about its research opportunities and foreseeable limitations.